2019
DOI: 10.1039/c9ra06114b
|View full text |Cite
|
Sign up to set email alerts
|

Normal vibrations of ternary DOPC/DPPC/cholesterol lipid bilayers by low-frequency Raman spectroscopy

Abstract: Upon lipid raft formation, the Raman peak corresponding to monolayer normal mechanical vibrations drops remarkably in position and width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…21 The latest research applied low-frequency Raman spectroscopy to show that the high cholesterol concentration induces a small interleaflet coupling. 31 Our AFM image supports the uncoupling event, so it is believed that the interleaflet coupling varies with the cholesterol concentration. Our results demonstrated that the cholesterol affects the mechanical property of the artificial bilayer and the spatial distribution of phospholipid.…”
Section: ■ Results and Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…21 The latest research applied low-frequency Raman spectroscopy to show that the high cholesterol concentration induces a small interleaflet coupling. 31 Our AFM image supports the uncoupling event, so it is believed that the interleaflet coupling varies with the cholesterol concentration. Our results demonstrated that the cholesterol affects the mechanical property of the artificial bilayer and the spatial distribution of phospholipid.…”
Section: ■ Results and Discussionsupporting
confidence: 69%
“…The recent uncoupling effect of DOPC bilayers was reported by observation of a bifurcation feature in the breakthrough force . The latest research applied low-frequency Raman spectroscopy to show that the high cholesterol concentration induces a small interleaflet coupling . Our AFM image supports the uncoupling event, so it is believed that the interleaflet coupling varies with the cholesterol concentration.…”
Section: Resultssupporting
confidence: 67%
“…In the present work, we employ a recently developed novel experimental approachlow-frequency Raman spectroscopy. In this approach, instead of studying atomic vibrations as is performed in conventional Raman spectroscopy, mechanical vibrations of the whole bilayer are detected. These vibrations appear between 5 and 90 cm –1 ; a narrow peak found in these experiments between 9 and 18 cm –1 (depending on the system and temperature) is attributed to an eigenmode of the normal vibrations of a lipid monolayer (i.e., of a leaflet).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, this is a breathing-type mode of a single monolayer as a continuous thick plate with displacements in the normal direction. Using this approach for model biological membranes, new information on lipid–cholesterol interactions was obtained , which may appear useful for elucidating the problem of lipid raft formation (see, e.g., ref for recent references).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation